School Administration System Based on Website (Case Study: MTs Al-Kautsar) - Wulandari, Berliana; Hidayat, Safaruddin; Afifuddin, Muhammad (IJISTECH (International Journal of Information System and Technology), 2024)
Schools, as institutions in the field of education, engage in extensive administrative data processing, including student data, teacher information, employee records, student grades, and tuition payment data. The volume of this data is substantial, necessitating efficient storage and administration. Currently, many schools manage administrative data manually, relying on ledger books and stacks of paper stored in file cabinets. This manual system has inherent weaknesses. The problem addressed is how to design a web-based administrative system to efficiently and accurately manage student, teacher, employee, assessment, payment, and payment report data according to specific needs. The chosen system development method is the Waterfall model, with the Unified Modeling Language (UML) as the analysis and design tool. The database is designed using phpMyAdmin in the WampServer application. The programming language employed is PHP (Hypertext Preprocessor), and the database is implemented using MySQL. Blackbox testing is utilized as the testing method. The goal is for this system to assist MTs Al-Kautsar Bogor in managing administration more effectively and efficiently.